Uncertainty in data envelopment analysis : fuzzy and belief degree-based uncertainties /: fuzzy and belief degree-based uncertainties. (2023) - Lotfi, Farhad Hossein Zadeh, 1967-; Sanei, Masoud; Hosseinzadeh, Ali Asghar; Niroomand, Sadegh; Mahmoodirad, Ali
No abstract available